Implementation of Bi'ah Lughawiyah in Improving Maharah Kalam at Modern Pondok Az-Zahra al-Gontory Purwokerto|Implementasi Bi’ah Lughawiyyah dalam Peningkatan Maharah Kalam di Pondok Modern Az-Zahra al-Gontory Purwokerto - Nia Himatul Ulya; Chairani Astina; Ashief El Qorny (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This research was motivated by the results of a survey of researchers at Pondok Modern Az-Zahra Al-Gontory Purwokerto who applied bi'ah lughawiyah in their daily activities. This research aims to: (1) Knowing the implementation of bi'ah lughawiyah at Pondok Modern Az-Zahra Al-Gontory Purwokerto. (2) Knowing the role of bi'ah lughawiyah in increasing maharah kala>m at the Modern Pondok Az-Zahra Al-Gontory Purwokerto. (3) Knowing the supporting factors and inhibiting factors in the application of bi'ah lughawiyah to the increase in maharah kala>m at the Modern Pondok Az-Zahra Al-Gontory Purwokerto. To achieve this goal, a descriptive qualitative research type with field research methods was used. The subjects in this study were the head of the boarding school, the administrator of the language department, and several students. Data was collected through participatory observation, in-depth interviews, and documentation, after which the data were analyzed and conclusions were drawn. The conclusions drawn from this study are (1) the implementation of bi'ah lughawiyah, namely by requiring the use of Arabic 24 hours a day, in learning at Pondok and Schools so that students are accustomed to using Arabic. (2) Bi'ah lughawiyah is very instrumental in increasing maharah kala>m, with one year of language habituation they have been able to communicate Arabic fluently. (3) Supporting factors are the existence of a supportive environment, cooperation, competent Arabic educators, and institutions language. The inhibiting factors are the lack of awareness of communicating in Arabic and lack of enthusiasm.